Proceedings of the 14th International Meshing Roundtable - Hanks, Byron W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
This volume presents results of the International Meshing Roundtable conference organized by Sandia National Laboratories held in September 2005. The conference is held annually and since its inception eleven years ago has become widely recognized as a major forum for the exchange of ideas in this field. The papers of this proceedings are devoted to mesh generation and adaptation which has applications to finite element simulation as well as to computational geometry and computer graphics. This book introduces theoretical and novel ideas with practical potential as well as technical applications from industrial researchers, bringing together renown specialists from engineering, computer science and mathematics.
Design and Implementation of a Corporate Mesh Object -- Session 1B -- Unstructured Computational Meshes for Subdivision Geometry of Scanned Geological Objects -- Automatic Near-Body Domain Decomposition Using the Eikonal Equation -- Marching Generation of Smooth Structured and Hybrid Meshes Based on Metric Identity -- A Hybrid Meshing Scheme Based on Terrain Feature Identification -- Interface Reconstruction in Multi-fluid, Multi-phase Flow Simulations -- Session 2 -- Meshing Piecewise Linear Complexes by Constrained Delaunay Tetrahedralizations -- Delaunay Refinement by Corner Lopping -- Robust Construction of 3-D Conforming Delaunay Meshes Using Arbitrary-Precision Arithmetic -- Meshing Volumes Bounded by Smooth Surfaces -- An Approach for Delaunay Tetrahedralization of Bodies with Curved Boundaries -- Identifying and Meshing Thin Sections of 3-d Curved Domains -- Session 3A -- Stitching and Filling: Creating Conformal Faceted Geometry -- Polygon Crawling: Feature-Edge Extraction from a General Polygonal Surface for Mesh Generation -- Generation of Mesh Variants via Volumetrical Representation and Subsequent Mesh Optimisation -- Structured Grid Generation over NURBS and Facetted Surface Patches by Reparametrization -- A Computational Framework for Generating Sizing Function in Assembly Meshing -- Session 3B -- A fews snags in mesh adaptation loops -- On discrete boundaries and solution accuracy in anisotropic adaptive meshing -- Weighted Delaunay Refinement for Polyhedra with Small Angles -- Polygonal Surface Remeshing with Delaunay Refinement -- Session 4B -- An All-Hex Meshing Strategy for Bifurcation Geometries in Vascular Flow Simulation -- An Interior Surface Generation Method for All-Hexahedral Meshing -- Unconstrained Paving & Plastering: A New Idea for All Hexahedral Mesh Generation -- Adaptive Sweeping Techniques -- A new least-squares approximation of affine mappings for sweep algorithms -- Session 5 -- Surface Smoothing and Quality Improvement of Quadrilateral/Hexahedral Meshes with Geometric Flow -- Quality Improvement of Surface Triangulations -- Compact Array-Based Mesh Data Structures -- Parallel 2D Graded Guaranteed Quality Delaunay Mesh Refinement.
Keywords: Engineering; Computer simulation; Computer graphics; Applied mathematics; Engineering mathematics; Computational intelligence; Mechanics; Mechanics, Applied; Engineering; Computational Intelligence; Theoretical and Applied Mechanics; Applications of Mathematics; Simulation and Modeling; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books